2010
DOI: 10.1007/s11595-010-0059-2
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a laboratory aging method for the accelerated simulation of reclaimed asphalt

Abstract: The paper presented first results elaborated during the European Research Project Re-road which aims at the development of techniques for increasing the recycling rates of reclaimed asphalt. During service life surface asphalt courses are subjected to aging due to oxidation effects which causes the hardening of the binder and thereby a change in the chemical, physical and mechanical properties of the material. Surface courses often contain highly modified binders as well as special additives for improving the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…It is also quite challenging to investigate due to the various variables such as precipitation, temperature, sunlight (UV), wind and others (Mouillet et al, 2009;Garrick, 1994). Therefore, many researchers have diverted their attention and proposed substantial evaluation tests and parameters to assess the ageing behaviour and ageing resistance of bitumen (Akbarnejad, Houben, & Molenaar, 2014;Mollenhauer, Pierard, Tusar, Mouillet, & Gabet, 2010;Li, Zhang, & Wang, 2007;Zhang, Liang, & Li, 2005;Airey, 2003;Shenoy, 2002). Lu, and Isacsson (2002) observed that bitumen ageing may be affected concurrently by numerous factors, such as bitumen content and properties, aggregate nature and particle size distribution, air voids, factors related to production, and external conditions such as time and temperature.…”
mentioning
confidence: 99%
“…It is also quite challenging to investigate due to the various variables such as precipitation, temperature, sunlight (UV), wind and others (Mouillet et al, 2009;Garrick, 1994). Therefore, many researchers have diverted their attention and proposed substantial evaluation tests and parameters to assess the ageing behaviour and ageing resistance of bitumen (Akbarnejad, Houben, & Molenaar, 2014;Mollenhauer, Pierard, Tusar, Mouillet, & Gabet, 2010;Li, Zhang, & Wang, 2007;Zhang, Liang, & Li, 2005;Airey, 2003;Shenoy, 2002). Lu, and Isacsson (2002) observed that bitumen ageing may be affected concurrently by numerous factors, such as bitumen content and properties, aggregate nature and particle size distribution, air voids, factors related to production, and external conditions such as time and temperature.…”
mentioning
confidence: 99%